Rancang Bangun Sistem Inventori Berbasis Android (Studi Kasus : Bengkel Setia Motor) - Faroek, Dewi Astria; Soekarta, Rendra; Elrico (Universitas Muhammadiyah Sorong, 2023)
Inventory is a very crucial and basic issue in all types of business, namely the inventory problem. This is because inventory is one of the determining factors for the smooth running of the production and sales process. So it is important to manage inventory well. Currently, the Setia Motor Workshop still uses manual recording methods to register goods in and out of the warehouse. With manual data collection, Setia Motor Workshop always takes the time to check goods efficiently, sometimes the existing stock of goods does not match the data they have recorded. The solution to this problem is to create an inventory system application that is able to summarize inventory at the Setia Motor workshop. In this research, the waterfall method was used. Based on the results of this research, the design and implementation of the inventory system at the loyal motorbike repair shop went very well, the system was designed based on the method steps used, so that this application can overcome the problems that occur. in data processing conditions at a loyal motorbike repair shop.